The general characteristics of swimming education programs in europe - LEN learn to swim sub-commission report - Štrumbelj, B.; Costa, A.; McMorrow, M. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
The most recent scientific evidence supports the importance of aquatic competence in reducing the risk of drowning, particularly in children (Campaniço, 2019). Proficiency in swimming is a prerequisite for safely engaging in sports such as water polo, synchronized swimming, diving, swimming itself, and other forms of water-based exercise, whether in competitive or recreational form. The learning of swimming has a long-standing tradition, as the first manual on swimming was published as far back as in the 1538 by Wynman (Pelayo,2003). Swimming has become an important cultural phenomenon where teaching is complex (Pelayo, 2003) According to Pelayo (2003) from 1538 to 1970 numerous writen works (more than 500 before 1900) have been published in relation to technical and teaching concepts. Since then, the methodology and didactics of swimming have evolved, making the process of learning to swim increasingly effective. Numerous studies have contributed to this development by investigating when and how it's most effective to start learning swimming (Stallman et al.,2017). However, these studies haven't provided unequivocal answers, leading different countries to approach swimming education in various ways. Some have left swimming instruction to parents, sports clubs, and other non-governmental organizations, while others have incorporated it into the school curriculum. Despite various efforts to encourage swimming education among the widest population, water-related fatalities still remain a significant issue across Europe and worldwide. Drowning is the third leading cause of unintentional injury death worldwide, accounting for 7% of all injury-related deaths (WHO, 2014). According to the WHO Global report on drowning (2014) age is one of the major risk factors for drowning. This relationship is often associated with a lapse in supervision. Globally, the highest drowning rates are among children 1-4 years, followed by children 5-9 years. Based on the available 2017 data, around 5 100 deaths of European Union (EU) residents were caused by accidental drowning and submersion (Eurostat, 2020). LEN (European Swimming Federation) serves as the governing body for aquatic sports in Europe and has established the Learn to Swim sub-commission. This sub-commission's task is to create a safe environment for engaging in swimming sports through the technical and scientific advice on the development of good practices for the massification of aquatic competences across all European member federations. The aim of this study was to understand the general characteristics of governmental and/or federative swimming education programs, national definitions of what constitutes being able to swim in single country as well as the current qualification and professional license requirements for swimming teachers in Europe.